Find
∫ − π π 1 + c o s 2 x 2 x ( 1 + s i n x ) . d x
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
You are missing an x in front of cos^2
I = ∫ − π π 1 + cos 2 x 2 x + 2 x sin x d x = ∫ − π π 1 + cos 2 x 2 x d x + ∫ − π π 1 + cos 2 x 2 x sin x d x But the function 1 + cos 2 x 2 x is odd thus its integral is equal to zero and the function 1 + cos 2 x 2 x sin x is even.
Therefore I = 0 + ∫ − π π 1 + cos 2 x 2 x sin x d x = 2 ∫ 0 π 1 + cos 2 x 2 x sin x d x ⇒ I = 4 ∫ 0 π 1 + cos 2 x x sin x d x
Define cos − 1 : [ − 1 , 1 ] → [ 0 , π ] which is the inverse function of cos : [ 0 , π ] → [ − 1 , 1 ]
Let x = cos − 1 u ⇔ u = cos x ⇔ d u = − sin x d x Then it is cos 0 = 1 and cos π = − 1 .Hence
I = 4 ∫ − 1 1 u 2 + 1 cos − 1 u d u
We know that the function sin : [ − 2 π , 2 π ] is odd thus
sin x = − sin ( − x ) , ∀ x ∈ [ − 2 π , 2 π ] ⇒ cos ( 2 π + x ) = − cos ( 2 π − x ) , ∀ x ∈ [ − 2 π , 2 π ]
Thus the function f ( x ) = cos ( 2 π − x ) , ∀ x ∈ [ − 2 π , 2 π ] is odd. Let g : [ − 1 , 1 ] → [ − 2 π , 2 π ] be the inverse function of f then g is also odd. And it holds that
g ( cos ( 2 π − x ) ) = x , ∀ x ∈ [ − 2 π , 2 π ] ⇒ g ( cos ( x ) ) = − x + 2 π , ∀ x ∈ [ 0 , π ] ⇒ g ( x ) = − cos − 1 x + 2 π , ∀ x ∈ [ − 1 , 1 ]
Therefore the integral equals to:
I = − 4 ∫ − 1 1 u 2 + 1 g ( u ) d u + 4 ∫ − 1 1 u 2 + 1 2 π d u
But the function x 2 + 1 g ( x ) is odd thus its integral is equal to zero. Lastly the given integral equals to:
I = 2 π ∫ − 1 1 u 2 + 1 1 d u = 2 π [ arctan u ] − 1 1 = 2 π ( 4 π − ( − 4 π ) ) = π 2
Problem Loading...
Note Loading...
Set Loading...
We use a particular property of definite integrals, namely: a ∫ b f ( x ) d x = a ∫ b f ( a + b − x ) d x
Moving on to the problem, consider the integral as I . Using the property mentioned above, we have,
I = − π ∫ π 1 + cos 2 x 2 x ( 1 + sin x ) d x = − − π ∫ π 1 + cos 2 x 2 x ( 1 − sin x ) d x ⟹ 2 I = − π ∫ π 1 + cos 2 x 2 x ( 1 + sin x − 1 + sin x ) d x ⟹ 2 I = − π ∫ π 1 + cos 2 x 4 x sin x d x
Now, this integrand is even and hence, we can simplify it as,
2 I = 2 ⋅ 0 ∫ π 1 + cos 2 x 4 x sin x d x ⟹ I = 0 ∫ π 1 + cos 2 x 4 x sin x d x
Using the property mentioned at the very beginning, the integral can be written as,
I = 0 ∫ π 1 + cos 2 x 4 π sin x − I ⟹ 2 I = 4 π ⋅ 0 ∫ π 1 + cos 2 x sin x d x
Make the substitution t = ( − cos x ) and d t = sin x d x to get,
2 I = 4 π ⋅ − 1 ∫ 1 1 + t 2 d t
This integrand is again even and also we can easily identify the integrand to be the derivative of arctan t . Hence, we have,
2 I = 8 π ⋅ [ arctan t ] 0 1 = 8 π ( 4 π − 0 ) ⟹ I = π 2
This problem is a duplicate of this one and you can see there that this problem can also be solved using IBP but this approach is much more elementary and easy.
I posted my solution (this one) as a comment there as you can see if you open that problem and since nobody has posted a solution here, I'm copying my comment from there and posting it as a solution here. :)